JENIS DAN POLA PERTUMBUHAN IKAN YANG TERTANGKAP DI SUNGAI SERUAI DESA NAMU SURO KABUPATEN DELI SERDANG SUMATERA UTARA (Kinds of Fish Species and Growth Pattern of Fish that was Chaught at River Seruai, Namo Suro Village, Deli Serdang District of North Sum - Putra S. A Sihaloho; Hasan Sitorus; Rusdi Leidonald (AQUACOASTMARINE, 2017)
The objective of the research was to know the kinds of fish species and growth pattern of fish that was caught at the River Seruai, Namo Suro Village, Deli Serdang District of North Sumatera Province. The research was conducted by using field survey method on November to December, 2016. Parameters measured were length and weight of fish, condition factor, gonad maturity and water quality. Based on the research found four fish species i.e Baung (Mystus nemurus), Cencen (Mystacoleucus marginatus), Nila (Oreochromis niloticus), and Sibaro (Hampala macrolepidota). All of the fish had a negative allometric growth pattern. The highest value of condition factor found in Cencen fish (1,007) and the lowest value obtained in Sibaro fish (0,001). The correltion of Length and weight of all fish species was very strong wih correlation coefficient (R) and determinant coefficient (R2) approximately to value of 1.Keywords: Fish Species, Growth Pattern, River Serui, Deli Serdang.